PELATIHAN dan PENDAMPINGAN PENGGUNAAN MENDELEY BERBASIS SYNCHRONOUS dan ASYNCHRONOUS BAGI GURU PENDIDIKAN AGAMA KRISTEN - Jenri Ambarita; Febrianty (Balai Diklat Keagamaan Medan, 2022)
This study aims to improve the knowledge and skills of participants in using the Mendeley reference application. Based on the objectives, this study uses a participatory action research (PAR) research approach with diagnostic steps, action plans, action tacking, evaluation and reflection. Training and mentoring activities are carried out with asynchronous and synchronous methods with a total of 20 participants. Data collection techniques used interviews, observations, document studies and tests. All data obtained will be analyzed using qualitative descriptive analysis techniques. The results showed that there was an increase in knowledge and skills in using the Mendeley application. 100% of participants said they were satisfied with the training and assistance in using the Mendeley application.